Color stability of a nanofill composite: effect of different immersion media (Journal of Applied Oral Science, 2009)
OBJECTIVE: The aim of this in vitro study was to evaluate the color stability of a nanofill composite resin (Filtek Z350) in different immersion media. MATERIALS AND METHODS: Twelve resin-based composite specimens were prepared using a silicon cylindrical mold measuring ≅1mm of thickness and ≅ 10mm of diameter. Specimens were light-cured for 40 s from both sides using a LED Radii at 1400 mW/cm² and were randomized into 4 groups (n= 3) according to immersion media: coffee, yerba mate, grape juice or water (control solution). A digital spectrophotometer was used to evaluate the color changes at baseline and at 1-week after immersion in each solution. Specimens were stored in the different staining media for 4 h/day during 1 week. The color differences (DE) were analyzed by paired t-test and one-way ANOVA with complementary Tukey test (p;0.05) CONCLUSIONS: The findings of the present study suggest that the tested nanofill resin-based composite was susceptible to staining by substances present in the grape juice.